2023
DOI: 10.1101/2023.01.15.524001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryptochromes and UBP12/13 deubiquitinases antagonistically regulate DNA damage response in Arabidopsis

Abstract: Cryptochromes (CRYs) are evolutionarily conserved blue-light receptors that evolved from bacterial photolyases that repair damaged DNA. Today, CRYs have lost their ability to repair damaged DNA; however, prior reports suggest that human CRYs can respond to DNA damage. Currently, the role of CRYs in the DNA damage response (DDR) is lacking, especially in plants. Therefore, we evaluated the role of plant CRYs in DDR along with UBP12/13 deubiquitinases, which interact with and regulate the CRY2 protein. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…UBPs are involved in many plant hormone signaling pathways, including JA, BR, and ABA responses ( Jeong et al., 2017 ; Liu et al., 2022 ; Xiong et al., 2022 ). Recent studies have further revealed their roles in the regulation of DNA damage repair ( Hu et al., 2023 ) and ultraviolet radiation tolerance ( Al Khateeb et al., 2019 ). In addition, the same function can be modulated by different UBPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UBPs are involved in many plant hormone signaling pathways, including JA, BR, and ABA responses ( Jeong et al., 2017 ; Liu et al., 2022 ; Xiong et al., 2022 ). Recent studies have further revealed their roles in the regulation of DNA damage repair ( Hu et al., 2023 ) and ultraviolet radiation tolerance ( Al Khateeb et al., 2019 ). In addition, the same function can be modulated by different UBPs.…”
Section: Discussionmentioning
confidence: 99%
“…UBP12 and UBP13 are involved in ultraviolet radiation tolerance, possibly in a similar manner to the homolog USP7 in humans ( Al Khateeb et al., 2019 ). UBP12/13 oppose the roles of CRY in DNA damage response ( Hu et al., 2023 ). CRYs, which evolved from bacterial photolyases required for the repair of damaged DNA, enable plants to detect blue light and fine-tune growth and development ( Chaves et al., 2011 ).…”
Section: Stress Response Regulated By Ubpsmentioning
confidence: 99%
See 1 more Smart Citation